A Conceptual Paper on Cross-Border Vertical Integration of Thailand Firms in Southeast Asia Countries: Financial Perspectives. - Hokta, Jatuporn; Chu, Ei Yet (School of Social Sciences, USM, 2017)
A considerable number of established and successful Thailand firms have increased their investments in domestic and regional markets. Their international expansions could be due to positive drivers such as financial strength. But the financial factors which contribute to their markets expansions have not been thoroughly explored. Thus, this study examines the effects of financial perspectives on cross-border vertical integration of Thailand firms in Southeast Asia countries, and applies the theory of coinsurance effects. Internationalization helps to reduce cost of capital and increases the availability of getting additional financing. The variables used in measuring finance perspectives include profitability, liquidity, firms’ leverage and foreign exchange rate. Moreover, the study seeks to investigate the impact of vertical integration on the performance of Thailand firms in ASEAN countries. In achieving these objectives, the study also accounts for firm size, firm age, cultural distance, geographic distance and Gross Domestic Products. The study plans to employ regression analysis on panel data for 2012-2016 period using secondary data from 48 Thailand firms with vertical integration and 50 firms with nonvertical integration. The study also assesses the effectiveness of vertical integration in South East Asian countries by comparing their impacts on short-term and long-term. This study has fundamental implications because it emphasizes the financial factors which affect higher valueadded and effective firms’ performance as firms expand through cross-border business. The finding would be useful to stakeholders in decision-making within the context of cross-border vertical integration. From the findings, the study makes some recommendations.